Health-related quality of life in patients with COVID-19; international development of a patient-reported outcome measure - Cecilie Delphin Amdal; Katherine Taylor; Dagmara Kuliś; Ragnhild Sørum Falk; Andrew Bottomley; Juan Ignacio Arraras; James Harold Barte; Anne Sophie Darlington; Kristin Hofsø; Bernard Holzner; Nina Marie Høyning Jørgensen; Melissa Paulita Mariano; et al. (SpringerOpen, 2022)
Abstract Background We aimed to create a questionnaire to assess the health-related quality of life including functioning, symptoms, and general health status of adult patients with current or previous COVID-19. Here, we report on Phase I and II of the development. Methods Internationally recognized methodology for questionnaire development was followed. In Phase I, a comprehensive literature review was performed to identify relevant COVID-19 issues. Decisions for inclusion, exclusion, and data extraction were completed independently in teams of two and then compared. The resulting issues were discussed with health care professionals (HCPs) and current and former COVID-19 patients. The input of HCPs and patients was carefully considered, and the list of issues updated. In Phase II, this updated list was operationalized into items/questions. Results The literature review yielded 3342 publications, 339 of which were selected for full-text review, and 75 issues were identified. Discussions with 44 HCPs from seven countries and 52 patients from six countries showed that psychological symptoms, worries, and reduced functioning lasted the longest for patients, and there were considerable discrepancies between HCPs and patients concerning the importance of some of the symptoms. The final list included 73 issues, which were operationalized into an 80-item questionnaire. Conclusion The resulting COVID-19 questionnaire covers health-related quality of life issues relevant to COVID-19 patients and is available in several languages. The next steps include testing of the applicability and patients' acceptability of the questionnaire (Phase IIIA) and preliminary psychometric testing (Phase IIIB).